2016
DOI: 10.1080/10286020.2016.1217519
|View full text |Cite
|
Sign up to set email alerts
|

Four new taraxastane-type triterpenoic acids from Cirsium setosum

Abstract: Four new taraxastane-type triterpenoids acids 3β,22α-dihydroxy-20-taraxasten-30-oic acid (1), 3β-hydroxy-22-oxo-20-taraxasten-30-oic acid (2), 3-oxo-22α-hydroxy-20- taraxasten-30-oic acid (3), and 3β,19β-dihydroxy-20-taraxasten-30-oic acid (4) were isolated and characterized from Cirsium setosum (Willd.) MB. Their structures were determined by the combination of 1D and 2D NMR experiments ((1)H-(1)HCOSY, HSQC, HMBC and ROESY) and mass spectrometry. Compound 2 exhibited potent selective cytotoxicity against huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The extracts of C. setosum have been marked in the U.S. as supplements for liver and cardiovascular disease [3], and in China as healthcare beverages for hypoglycemic, hypolipidemic, and anti-inflammatory effects [4,5,6,7]. Phytochemical studies on C. setosum revealed that it contained triterpenes, flavonoids, sterols, polyphenols, and glycosides [1,2,8,9]. These components have been shown to have various bioactivities, including antihemorrhagic, anti-inflammatory, antioxidant, and antimicrobial activities [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The extracts of C. setosum have been marked in the U.S. as supplements for liver and cardiovascular disease [3], and in China as healthcare beverages for hypoglycemic, hypolipidemic, and anti-inflammatory effects [4,5,6,7]. Phytochemical studies on C. setosum revealed that it contained triterpenes, flavonoids, sterols, polyphenols, and glycosides [1,2,8,9]. These components have been shown to have various bioactivities, including antihemorrhagic, anti-inflammatory, antioxidant, and antimicrobial activities [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, C. setosum is widely used to treat many types of diseases, including incomplete uterine contraction and bleeding, infectious hepatitis, digestive tract bleeding, cardiovascular disease, and promote aggregation and adhesion of platelets (Lu et al 2015;Ma et al 2016a). Modern phytochemical studies revealed that triterpenes, flavonoids, sterols, polyphenols, and glycosides are its main medicinal ingredients (Luan et al 2016;Ma et al 2016b;Ma, Wen, et al 2016). However, little is known in its biosynthesis mechanism.…”
mentioning
confidence: 99%